Information seeking pattern in electronic environment of sciences and arts researchers: a comparative study (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
The purpose of this paper is to examine information seeking pattern of science and art research scholars and for this the data was gathered using questionnaire survey of 139 (one hundred and thirty-nine) randomly selected, PhD scholars of science and arts departments of Asia’s largest residential university Banaras Hindu University, India. It has been found that both the groups of researchers have some similarities and some dissimilarity in information seeking. Even in this electronic era some research scholars of art discipline depend on print form of publications for their information needs. Keywords: Information Seeking-Behavior. Electronic Environment. User Studies. Researcher Arts Area. Researcher Sciences Area. Link para o texto completo (PDF)http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/1290/2446